1997
DOI: 10.1097/00001756-199707070-00023
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides enhance KCl-induced Ca2+ influx and acetylcholine release in brain synaptosomes

Abstract: Effects of gangliosides GM1 and GQ1b on cholinergic synaptic functions were investigated using synaptosomes prepared from mouse brain cortices. Treatment of synaptosomes with GM1 and GQ1b increased high K(+)-evoked acetylcholine (ACh) release in a bell-shaped dose-dependent manner. The peaks of the effects were found to be at 1-5 microM for GM1 and 5-10 microM for GQ1b. ACh synthesis and the levels of ACh in synaptosomes were not affected by the ganglioside treatment. Both gangliosides enhanced depolarization-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 22 publications
3
25
1
Order By: Relevance
“…However, we found no major synaptic deficits in both null-mutants. This is quite surprising, in view of studies suggesting a synaptic role for gangliosides on the basis of exogenous ganglioside application (Tanaka et al, 1997;Ando et al, 1998), as well as the reported co-localization in lipid rafts of gangliosides and proteins important for neuroexocytosis (Chamberlain et al, 2001;Lang et al, 2001;Taverna et al, 2004;Salaun et al, 2004). The only changes we observed were some extra degree of rundown of transmitter release at high intensity use at the dKO NMJ and a temperature-specific increase in quantal content at 35 C in GD3s-KO NMJs, compared to WT.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, we found no major synaptic deficits in both null-mutants. This is quite surprising, in view of studies suggesting a synaptic role for gangliosides on the basis of exogenous ganglioside application (Tanaka et al, 1997;Ando et al, 1998), as well as the reported co-localization in lipid rafts of gangliosides and proteins important for neuroexocytosis (Chamberlain et al, 2001;Lang et al, 2001;Taverna et al, 2004;Salaun et al, 2004). The only changes we observed were some extra degree of rundown of transmitter release at high intensity use at the dKO NMJ and a temperature-specific increase in quantal content at 35 C in GD3s-KO NMJs, compared to WT.…”
Section: Discussioncontrasting
confidence: 57%
“…In the light of their known effects on ion-channels and their particular abundance in synaptic regions, gangliosides are thought to play a role in neurotransmitter release, which is critically dependent on presynaptic ion-channel function (Wieraszko and Seifert, 1985;Ramirez et al, 1990;Egorushkina et al, 1993;Takamiya et al, 1996;Tanaka et al, 1997;Furuse et al, 1998;Ando et al, 1998;Meir et al, 1999;Chiavegatto et al, 2000;Bullens et al, 2002;Hakomori, 2003;Proia, 2003). Several important proteins of the release machinery co-localize with gangliosides within lipid rafts (Chamberlain et al, 2001;Lang et al, 2001;Taverna et al, 2004;Salaun et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A presynaptic explanation for the changed EPP and MEPP kinetics and quantal size (e.g. increased filling of ACh vesicles) is less likely because gangliosides have been reported to lack effect on ACh synthesis (Tanaka et al, 1997). On the basis of the only relatively small magnitude of the observed kinetic changes of the EPPs and MEPPs in aged GD3s-KO mice, and the EPP amplitude being somewhat increased compared to wild-type, it is not to be expected that successful neuromuscular transmission is endangered.…”
Section: Discussionmentioning
confidence: 96%
“…Gangliosides may be particularly important in synaptic function because they 1) show high expression at synapses (Ando et al, 2004;Waki et al, 1994); 2) co-localize with neuroexocytotic proteins (Chamberlain et al, 2001;Lang et al, 2001;Salaun et al, 2004;Taverna et al, 2004) and 3) influence neurotransmitter release and synaptic plasticity when applied exogenously Egorushkina et al, 1993;Furuse et al, 1998;Ramirez et al, 1990;Tanaka et al, 1997;Wieraszko and Seifert, 1985). In spite of this, we recently showed near-normal synapse function at neuromuscular junctions (NMJs) of mice lacking either complex gangliosides, b/c-series gangliosides or all gangliosides except GM3 ( Fig.1) (Bullens et al, 2002;Zitman et al, 2008), suggesting neurotransmission was supported by GM3 alone or, alternatively, is ganglioside-independent.…”
Section: Introductionmentioning
confidence: 99%
“…Survival of BCG expressing neuronal cells is reasonable since several studies have suggested that complex gangliosides participate in synaptic functions, in particular for regulation of Ca 2ϩ -flux (42)(43)(44)(45). We will now investigate the molecular mechanisms for regulation of ceramide and BCG expression and further analyze the sphingolipid-regulated signaling pathways that are significant for neuronal development.…”
Section: Par-4 and Bcg Expression Is Correlated With Apoptosis And Cementioning
confidence: 99%